Transforming Challenges Into Opportunities: The Role Of Accounting Systems And Technology In MSME Performance Post-COVID-19, Enhanced By Market Innovation - Benny Oktaviano; Dian Sulistyorini Wulandari (Journal of Scientific Interdisciplinary, 2024)
This research explores the impact of technology adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the post-COVID-19 landscape, with a particular focus on the moderating role of market innovation. Utilizing a Structural Equation Modeling (SEM) approach, data was collected from MSMEs to evaluate the relationships among technology adoption, market innovation, and business performance. The findings reveal that technology adoption has a significant positive effect on MSME performance, contributing to operational efficiency and improved customer engagement. However, contrary to expectations, market innovation does not significantly moderate this relationship. This suggests that the immediate benefits of technology adoption are sufficient to drive performance improvements without the need for market innovation to enhance these effects. The research highlights the importance for MSMEs to prioritize technology adoption as a strategy for resilience and growth in the wake of the pandemic, while market innovation can be pursued as a complementary initiative for long-term competitiveness. The study provides valuable insights for policymakers and practitioners aiming to support the recovery and development of MSMEs in Indonesia.